Study on characteristics of patients with repeated admission for asthma in Hospital Tengku Ampuan Afzan, Kuantan, Pahang, Malaysia - Md Aris, Mohd Aznan; Ismail, Shaiful Bahari; Mohamad, Mohd Fauzi (Japan International Cultural Exchange Foundation (JICEF), 2005)
Objective: To determine the characteristics among patients with repeated admissions for asthma compared with patients with no repeated admission for asthma over the same period of one-year duration. Methods: A cross-sectional comparative study among 30 patients with asthma who had repeated admissions with another 30 patients with asthma who had no repeated admission for exacerbation of asthma over a same period of one-year duration (2001). The socio-demographic, clinical characteristics and evaluation data were collected. An evaluation included measurement of peak expiratory flow (PEF), inhaler technique skills and questionnaires on knowledge of asthma. Results : There were no significant differences in socio-demographic characteristics, measurement of PEF and inhaler technique skill in between both groups. In clinical characteristics, there were significant differences in duration of asthma, history of atopy, history of absenteeism, asthma symptoms and use of medications. There was significant difference between groups in their knowledge of asthma where the total mean scores of both groups were 14.8 in repeated admissions group and 17.7 in non - repeated admission group from the total score of 31. Conclusions: Patients with repeated admissions for asthma tends to have less duration of asthma, high past history of atopy, high history of absenteeism from works or schools, more frequent nocturnal symptoms and more use of inhaler corticosteroids. They also had poor inhaler techniques and lesser asthma knowledge.